Sinnikäs kolonialismi: alkuperäiskansaisuus ja kehityksen politiikka - Lindroth, Marjo; Sinevaara-Niskanen, Heidi (Valtiotieteellinen yhdistys - Statsvetenskapliga föreningen, 2018)
Resilient colonialism: Indigeneity and the politics of development Rapid and unpredictable global changes have given birth to a political ethos of resilience. In themidst of calls for preparedness, international politics has re-discovered the (allegedly) innate qualitiesof indigenous peoples that enable them to adapt to and accommodate change. The peoples’exemplary resilience has been deemed empowering, not only for themselves, but for the planet asa whole. However, as we argue, the seemingly well-meaning and benign political celebration ofresilient indigeneity continues marginalization and othering, practices that are often considered tobelong to the colonial past. The article engages in a critical discussion on indigeneity, colonialismand resilience – topics that have yet to be brought into a dialogue with one another. With referenceto contemporary political initiatives of the United Nations and the Arctic Council, we illustrate theways in which the political focus on and desire for indigenous resilience continue the age-old expectationthat indigenous peoples will adapt, endure and persevere. Resilience enables colonialpractices to persist; it is yet another façade allowing those in power to continue to order time andto ignore the relevance of the past and current injuries indigenous peoples have endured. The violenceof resilience lies in its insistence that those whose only option so far has been to adapt continueto do so without any guarantees of better circumstances.